2002
DOI: 10.3168/jds.s0022-0302(02)74103-9
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Colostral Macromolecules into the Cerebrospinal Fluid via Plasma in Newborn Calves

Abstract: The objective of this study was to investigate the transfer of bovine colostral macromolecules especially the lactoferrin (Lf), transferrin (Tf), immunoglobulin G (IgG), and epidermal growth factor (EGF) from the gastrointestinal tract to the cerebrospinal fluid (CSF) via systemic circulation in newborn calves. Cannulae were placed into the jugular vein and cisterna magna to collect blood and CSF, respectively at various time points. The colostrum, plasma, and CSF were analyzed by ELISA, SDS-PAGE, two-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
2
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 26 publications
4
40
2
2
Order By: Relevance
“…Previously, we reported that orally administered of BLF entered the CSF in piglets [10] and calves [21]. In the preliminary study, we also detected the presence of BLF in rat CSF following oral or intraperitoneal administration.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Previously, we reported that orally administered of BLF entered the CSF in piglets [10] and calves [21]. In the preliminary study, we also detected the presence of BLF in rat CSF following oral or intraperitoneal administration.…”
Section: Discussionmentioning
confidence: 60%
“…Lactoferrin is a ubiquitous protein which exists in milk, plasma, synovial fluids, cerebrospinal fluid (CSF), and other biological fluids [3, [14][15][16]21]. Under inflammatory conditions, LF production is increased in the periphery by neutrophils [2,14] and in the central nervous system (CNS) by microglia [8].…”
mentioning
confidence: 99%
“…The average protein content of colostrum is represented mainly by Ig, which has the important function of helping to combat microorganisms during the first days of life in a newborn calf (Weaver et al, 2000). Moreover, proteins from colostrum serve as a source of amino acids, although they can also play the role of meeting energy requirements (Talukder et al, 2002). Kehoe et al (2007) found a protein content of 14.9% and emphasized that this component has little influence of feeding but more of parity of cows.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the lipid content, lactose, despite its low colostrum concentration (2.7%), has also an important function in the energy supply of newborns (Davis and Drackely, 1998). Another group that contributes to good newborn development is non-immunoglobulin proteins, which facilitate nutrient absorption and provide amino acids for development of the gastrointestinal tract (Talukder et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, opioids also act in the CNS and cause systemic hypotension (11,39). On the other hand, LF and its receptor have also been identified in the CNS (13,15,16,24,25,32,33,41). Recently, we reported that BLF produces -opioid receptormediated antinociceptive activity (19), and this BLF-induced analgesia is mediated by NO production (20).…”
mentioning
confidence: 99%